Maize (zea mays l) landraces from the southern region of Brazil: contamination by fusarium sp, zearalenone, physical and mechanical characteristics of the kernels - Oliveira, Tatiana Roselena de; Jaccoud Filho, David de Souza; Henneberg, Luciana; Michel, Milton Domingos; Demiate, Ivo Mottin; Pinto, Alessandra Teixeira Barbosa; Machinski Junior, Miguel; Barana, Ana Cláudia (My University, 2009)
This work had as objectives the study of the physical and mechanical characteristics of maize kernels in relation to the contamination by Fusarium sp and by zearalenone in twenty landraces of maize from the southern region of Brazil. From the analyzed samples, 60 % has been considered to have a hard endosperm type and 40 % an intermediary one. A correlation between the physical and mechanical variables was observed as an indication that the higher is the proportion of hard endosperm, more dense will be the kernel and more force for its rupture will be necessary. The level of contamination by Fusarium sp was between 5.5 and 24.75% among the analyzed grains, correlating positively with the flotation index, indicating that the landraces of maize with a softer endosperm can present a higher contamination by this genus. The presence of zearalenone was verified in 75 % of the samples, in concentrations varying from 50 to 640 µg kg
Keywords: Fungi; Texture of endosperm; Corn landraces; Mycotoxins